2010
DOI: 10.1029/2009jd013408
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of climate change, stomatal closure, and leaf area index changes to 20th and 21st century runoff change: A modelling approach using the Organizing Carbon and Hydrology in Dynamic Ecosystems (ORCHIDEE) land surface model

Abstract: [1] The recent evolution of continental runoff is still an open question. A related and controversial question is the attribution of this change and its consequences on our predictions of the behavior of future runoff. Here, the Land Surface Model Organizing Carbon and Hydrology in Dynamic Ecosystems is used to perform a set of transient simulations of the runoff from 1900 to 2100. We first show that the model's simulated runoff increases for the 20th century from a global point of view as well as its geograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 28 publications
(58 reference statements)
4
43
1
Order By: Relevance
“…Rising CO 2 concentration could alter vegetation water use (and thus the water cycle) through two opposite effects (Tubiello et al, 2007;Leakey, 2009;Alkama et al, 2010): (i) lower stomatal conductance which leads to a reduction in potential evapotranspiration (PET) and (ii) enhanced photosynthesis which leads to an increase in leaf area index and an increase in PET. Even though the effects of increased atmospheric CO 2 levels on discharge remain highly uncertain, some global studies like Gerten et al (2008) and Shi et al (2011) have demonstrated that this carbon effect may have had a non-negligible impact on runoff.…”
Section: Carbon Effect On Plant Water Usementioning
confidence: 99%
“…Rising CO 2 concentration could alter vegetation water use (and thus the water cycle) through two opposite effects (Tubiello et al, 2007;Leakey, 2009;Alkama et al, 2010): (i) lower stomatal conductance which leads to a reduction in potential evapotranspiration (PET) and (ii) enhanced photosynthesis which leads to an increase in leaf area index and an increase in PET. Even though the effects of increased atmospheric CO 2 levels on discharge remain highly uncertain, some global studies like Gerten et al (2008) and Shi et al (2011) have demonstrated that this carbon effect may have had a non-negligible impact on runoff.…”
Section: Carbon Effect On Plant Water Usementioning
confidence: 99%
“…The factor separation methodology from Stein and Alpert (1993) and Alkama et al (2010) is used to categorize the contributions of climate change, CO 2 fertilization, and LAI, as well as their interactions to long-term trends of ET and GPP. Similar to Alkama et al (2010), the total effect, f 123 , is expressed as…”
Section: Separation Of Climate Change and Management Effectsmentioning
confidence: 99%
“…Climate change dominated the interannual variability of ET, while land use changes and agricultural practices and techniques exerted more discernable effects on the water cycle in the long term . However, Alkama et al (2010) and Shi et al (2011) demonstrate that climate change is the predominant driver of the global ET tendency in the 20th century. Commonly, the contributions of climate change to vegetation productivities on a large scale are quantified by the ecosystem models or statistical models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dai et al, 2009;Alkama et al, 2010Alkama et al, , 2011, it appears that the precise contribution of natural vs. anthropogenic drivers, and of changes in vegetation, to variations and trends in global discharge currently cannot be quantified on solid grounds. Even the existence of an upward global trend is hardly detectable with confidence.…”
Section: Effects Of Land Cover and Land Use Changes In The Global Watmentioning
confidence: 99%